Review on CFD based models for co-firing coal and biomass. (November 2015) - Tabet, F.; Gökalp, I.
Abstract: Biomass co-firing within the existing infrastructure of pulverized coal utility boilers is viewed as a practical near-term means of encouraging renewable energy while minimizing capital requirements and maintaining the high efficiency of pulverized coal boilers. Coal/biomass co-firing is a complex problem that involves gas and particle phases, along with the effect of turbulence on chemical reactions. Computation Fluid Dynamic (CFD) simulations can provide insight to design and operational issues, such as co-firing percentage, load swings, injection location, excess air and air/fuel staging, and predictions related to heat release, unburned carbon, and NOx emissions. The CFD based co-firing tools consist of models for turbulent flow, gas phase combustion, particles dispersion by turbulent flow, coal/biomass particles devolatilization, heterogeneous char reaction and radiation. Additional models related to slagging and fouling can also be found. This paper presents a review on CFD based modeling approaches used to predict the combustion characteristics of co-firing biomass with pulverized coal under air and oxy-fuel conditions.